RAAV-compatible MiniPromoters for restricted expression in the brain and eye. Issue 1 (December 2016) - de Leeuw, Charles; Korecki, Andrea; Berry, Garrett; Hickmott, Jack; Lam, Siu; Lengyell, Tess; Bonaguro, Russell; Borretta, Lisa; Chopra, Vikramjit; Chou, Alice; D'Souza, Cletus; Kaspieva, Olga; et al.
Abstract Background Small promoters that recapitulate endogenous gene expression patterns are important for basic, preclinical, and now clinical research. Recently, there has been a promising revival of gene therapy for diseases with unmet therapeutic needs. To date, most gene therapies have used viral-based ubiquitous promoters–however, promoters that restrict expression to target cells will minimize off-target side effects, broaden the palette of deliverable therapeutics, and thereby improve safety and efficacy. Here, we take steps towards filling the need for such promoters by developing a high-throughput pipeline that goes from genome-based bioinformatic design to rapid testing in vivo. Methods For much of this work, therapeutically interesting Pleiades MiniPromoters (MiniPs; 4 kb human DNA regulatory elements), previously tested in knock-in mice, were "cut down" to 2.5 kb and tested in recombinant adeno-associated virus (rAAV), the virus of choice for gene therapy of the central nervous system. To evaluate our methods, we generated 29 experimental rAAV2/9 viruses carrying 19 different MiniPs, which were injected intravenously into neonatal mice to allow broad unbiased distribution, and characterized in neural tissues by X-gal immunohistochemistry for icre, or immunofluorescent detection of GFP. Results The data showed that 16 of the 19 (84 %) MiniPs recapitulated the expression pattern of their design source. This included expression of: Ple67 in brain raphe nuclei; Ple155 in Purkinje cells of the cerebellum, and retinal bipolar ON cells; Ple261 in endothelial cells of brain blood vessels; and Ple264 in retinal Müller glia. Conclusions Overall, the methodology and MiniPs presented here represent important advances for basic and preclinical research, and may enable a paradigm shift in gene therapy.